An initial investigation of improving acute care for hearing-impaired patients through the use of a transparent surgical mask - Bradbury, Karen; Pines, Rachyl (Communication and Medicine, 2022)
There is a general assumption that, in the hospital setting, standard surgical masks, unlike transparent masks, prevent effective communication with the hearing-impaired. This study investigates the experience of healthcare professionals (HPs) and hearing-impaired patients using a transparent surgical mask vs. a standard surgical mask in an acute care hospital. Our study design used a cross sectional, mixed-methods survey of 25 adult hearing-impaired patients/visitors and 36 HPs caring for them while wearing a transparent mask. The results demonstrated that 89% of staff and 76% of patients said the mask improved communication. This improvement was due to better ability to interpret nonverbal cues, which led to less need for repetition or volume increase. It was found that 69% of staff said the mask was comfortable and 81% were satisfied; 64% of patients liked being able to see facial expressions of the person wearing the mask; 72% of patients felt more connected to, and 76% understood the speech of, the person using the mask; and 80% of patients and 78% of staff preferred the transparent mask. The findings suggest that hospital staff/providers should use a mask with a clear window around the mouth and face while caring for hearing-impaired patients. This may improve patient satisfaction and prevent errors that are due to miscommunication.